2020
DOI: 10.3389/fonc.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of the Human Microbiome in Ovarian Cancer

Abstract: Ovarian cancer is the most lethal malignancy among gynecological cancers worldwide. Most ovarian cancer patients are diagnosed at an advanced stage because of non-specific clinical symptoms. The human microbiome plays a crucial role in maintaining the normal physiological and pathological state of the body. With the development of technologies such as DNA and 16S rRNA sequencing, an increasing number of findings on the role of microbiome in cancers are being reported. Microbiome abnormalities are increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 90 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…Although the underlying mechanisms of ascites development are largely unknown, previous studies have reported that immune cells such as Th17 T cells, NK cells and macrophages found in peritoneal ascites may play a key role in tumor cell invasiveness and growth (27)(28)(29)(30). To this end, we analyzed the immune cell populations within the peritoneal ascites uid through ow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Although the underlying mechanisms of ascites development are largely unknown, previous studies have reported that immune cells such as Th17 T cells, NK cells and macrophages found in peritoneal ascites may play a key role in tumor cell invasiveness and growth (27)(28)(29)(30). To this end, we analyzed the immune cell populations within the peritoneal ascites uid through ow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian cancer is among the most prevalent cancers in women ( Cheng et al, 2020 ). The TME has a major impact on tumor progression, recurrence, and metastasis, resulting in poor prognosis ( Chen et al, 2019 ; Huang et al, 2019 ; Zhang F.-P. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TLR2, 4, and 5 culminate in the activation of inflammation-associated cytokine signaling pathways in ovarian cancer and the adjacent tissues, leading to the activation of NF-kappa B signaling (Zhou 2019a ). Other pattern recognition receptors may be involved in ovarian cancer development (Cheng et al 2020 ), but the evidence for their involvement is weak. Tumor-associated macrophages have a pivotal role in driving ovarian cancer development (Xu et al 2019 ).…”
Section: Oncobiotic Transformation In Ovarian Cancermentioning
confidence: 99%
“…Pathogen colonization influences ovarian carcinogenesis, indicating that antibiotic use in ovarian cancer may inhibit cancer cell movement and metastasis formation. However, we are not aware of any dedicated in vivo study to assess this possibility, nevertheless, the literature suggests that antibiotic treatment may impact on the gut microbiome and, hence modulate the polarization of the immune system, and through that inflammation promoting ovarian cancer (Cheng et al 2020 ).…”
Section: Modulating the Oncobiome In Ovarian Cancermentioning
confidence: 99%